Seismic vulnerability analysis of reinforced concrete frame with infill wall considering in-plane and out-of-plane interactions (Fracture and Structural Integrity, 2022)
The seismic performance of a building hinges on the seismic capacity and damage features of the reinforced concrete (RC) frame with masonry infill walls. To reasonably evaluate the seismic performance and seismic economic loss of masonry infill walls, it is necessary to consider the in-plane (IP) and out-of-plane (OOP) interactions of these walls under seismic actions, and to model the vulnerability of the infill walls and the frame. Based on the test data on masonry infill walls, this paper designs a performance indicator for infill wall in the light of IP-OOP interactions, and determines the response threshold of each damage state. With the aid of OpenSees, the authors developed and verified a reasonable modeling method for RC frames with infill walls. As per the current code in China, a 5-storey RC frame with infill walls was designed, and two three-dimensional (3D) space models were established for the structure by the proposed modeling method. One of them considers IP-OOP interactions, and the other does not. Then, the structure was subjected to incremental dynamic analyses (IDA), and different damage indicators were determined to examine the damage of the infill walls and the overall structure, producing a set of vulnerability curves. The results show that the consideration of IP-OOP interactions significantly increases the probability of seismic damages on the infill walls and the overall structure. The most prominent increase was observed in the medium to serious damage stages.
Keywords: Masonry infill walls; Reinforced concrete (RC) frame; In-plane (IP) and out-of-plane (OOP) interactions; Damage indicators; Seismic vulnerability analysis